Magistério e distinção: um estudo sobre as trajetórias das professoras ganhadoras do Prêmio Professores do Brasil no meio oeste de Santa Catarina - Koga, Yáscara Michele Neves (2009)
The research central issue is the profile of the teacher who works at the public Elementary School from 1st to 4th grades at the state of Santa Catarina, the winner of the Prize Professores do Brasil (Teachers of Brazil). The study was carried out considering the sociological perspective. The research is based on Pierre Bourdieu s theory about the social capital, cultural capital and distinction. Aiming to define the profile and analyze the conditions of the granted teachers professional trajectory, we analyzed aspects related to: social origin, trajectory, teaching formation; cultural capital; mobilization to do the prize subscription; distinction among the other colleagues. From March 2007 to September 2008 we carried out interviews and questionnaires in two granted teachers who lived at the city of Vargem Bonita- SC, the only city with two citizens who had been granted with the Prize Teachers of Brazil at the Midwest of Santa Catarina. Besides, we researched the Prize Teachers of Brazil in 2003 and 2004, aiming to define what is considered worth of distinction by the Ministry of Education. The research data evidenced that the teachers who participated in the Prize Teachers of Brazil had a certain degree of cultural and social capital. The data also allowed us to understand that the participants of the awards used to value in their school and family trajectory the search for grants. We also realized that there is the legitimization of the teacher as the main agent of the change of quality of the public teaching in Brazil, according to the Ministry of Education. The granted teacher is the center of the solutions . In many cases, the teachers involve the community in order to help renovating the physical spaces or to donate the necessary resources to the teaching profession